Estruturas supramoleculares de nucleosídeos mimetizando DNA em cristais: forma III da dupla hélice de lamivudina - Vasconcelos, Alline Torquato (2014)
Lamivudine (β-L-2',3'-dideoxy-3'-thiacytidine, 3TC) is a nucleoside-based anti-HIV/HBV drug that has provided insights into the nucleic acid double-stranded helix assembly. Two crystal structures thereof assembled with nucleobase pairing and helical stacking as mimicries of DNA, but without the phosphodiester linkages in the fiber periphery, have recently demonstrated that nucleosides bring themselves the chemical information to assemble DNA duplexes even if the covalent backbone is absent. Here, we report the third structural example in which nucleosides are base-paired and helically base-stacked. A DNA-like double stranded helix was prepared cocrystallizing lamivudine with fumaric acid. We have named it as lamivudine duplex III. When substituting maleic acid present in the first example of lamivudine duplex for its trans-stereoisomer, the formation of a DNA-mimicry is still observed but with changes in the crystal stoichiometry, nucleobase pairing pattern and duplex backbone. Lamivudine duplex III exhibits both base pairing motifs present in the antecedent duplexes. In this structure, there are four protonated lamivudine molecules paired in-plane with four neutral ones. These crystallographically independent base pairs are held together through three hydrogen bonds as occurs in lamivudine duplex I made up of cytosine-cytosine+ base pairing only. But, contrarily to the duplex I with pairing between neutral and cationic drug units only, the duplex III has one neutral 3TC=3TC pair in its asymmetric unit. These molecules are kept in contact through only two peripheral N―H•••O hydrogen bonds as in two of the three neutral lamivudine pairs of the second example of lamivudine duplex. In both structures, each neutral pair is face-to-face stacked on top of one another and face-to-tail stacked on bottom of another one. Even in agreement with its higher structural complexity, the duplex III is present with very puckering conformations besides the three different orientations of the OH moiety at C5’. Five-membered oxathiolane ring adopts three envelop puckering modes and two twist conformations. This is the first report of a twist pucker for lamivudine despite of the large number of reported crystal structures thereof. Another remarkable characteristic of the duplex III is in its fiber periphery. There are hydrogen bonds between the 5’-OH moieties of neighbor pairs pointing in the direction of the missing phosphodiester linkages that would covalently bond two adjacent monomers in the strand. Furthermore, the geometry of these interactions reveals the antiparallel orientation of each strand relative to one another into the nucleoside duplex backbone. Noteworthy similarities between the duplexes crystallizing together with either hydrogen maleate or hydrogen fumarate are their left handedness and the outline of surface grooves of similar depth. But, while all hydrogen maleate counterions are lodged on the grooves of the duplex I, some hydrogen fumarate units are also interacting with themselves into one-dimensional chain of counterions. The third example of unusual double-stranded helices of lamivudine strengthens the fact that nucleosides can self-aggregate into DNA-like duplexes even without the covalent phosphodiester linkages in fiber periphery. Besides that, the structure described here adds knowledge on lamivudine versatility to assemble DNA-mimicry in crystals.